Mesenteric panniculitis in a patient with new onset dermatomyositis. Issue 1 (2nd February 2020) - Bansal, Pankaj; Gilbert, Emily L; Pereira, Rodrigo Otavio Lami; Virata, Andrew R
Abstract : Mesenteric panniculitis (MP), part of the spectrum of sclerosing mesenteritis, is an often asymptomatic disorder that is characterised by chronic inflammation of abdominal mesentery. We present a case of an 83-year-old woman who presented with proximal muscle weakness and erythematous, photosensitive rash of the face and upper torso and was subsequently diagnosed with dermatomyositis based on skin biopsy, electromyography and muscle biopsy. She had radiographic evidence of panniculitis on CT scan of the abdomen and pelvis for malignancy surveillance, which improved on serial CT scan 3 months after beginning treatment for her underlying dermatomyositis with prednisone and mycophenolate mofetil. Our case highlights that MP can be associated with underlying autoimmune disease. Connective tissue disease could be considered in the differential of MP when other etiologies such as surgery, trauma and malignancy are ruled out.